SAMPLE EQUALITY TEST IN BLENDED LEARNING USING GOOGLE CLASSROOM - Ayuningsih, Ni Putu Meina (Universitas Trunojoyo Madura, 2022)
Along with the recovery from the COVID-19 pandemic, the government expects the use of technology, information and communication (ICT) in innovative learning activities in schools. One of them is in the process of Limited Face to Face Learning (PTMT) mathematics in Vocational High Schools (SMK) to provide more opportunities for students to actively participate in each stage of learning. The quality of education is very dependent on the quality of learning carried out by teachers in the classroom. Optimization of the learning process can be done by integrating the use of technology as a learning medium, one of which is by using Google Classroom in blended learning at school. o find out the equality between classes in the population, a t-test was conducted. The results of the population equivalence test obtained that all students of Class XI SMK Wira Harapan for the academic year 2022/2023 were equal and the experimental group selected was X JB1 and the control group obtained X AP.